2003
DOI: 10.1007/s00420-003-0448-3
|View full text |Cite
|
Sign up to set email alerts
|

Workers' assessments of manual lifting tasks: cognitive strategies and validation with respect to objective indices and musculoskeletal symptoms

Abstract: Cognitive reasoning of experienced workers may be used as an active device for the evaluation of strenuous physical activities such as lifting tasks. Lifting activities are significantly associated with musculoskeletal symptoms, not only in the lower-back region, but also in seven other body parts; and effort may integrate the effects of both physical (lifting tasks) and non-physical (i.e., work dissatisfaction) factors, as well as perception of risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Loading metrics remained the most significant factors in explaining variance in the effort levels for all models. This agrees with an earlier study (Yeung et al 2003). They found that the weight in the hand was the most important factor in determining perceived effort for lifting tasks.…”
Section: Influence Of Subject and Task Parameters On Effort Perceptionsupporting
confidence: 90%
See 1 more Smart Citation
“…Loading metrics remained the most significant factors in explaining variance in the effort levels for all models. This agrees with an earlier study (Yeung et al 2003). They found that the weight in the hand was the most important factor in determining perceived effort for lifting tasks.…”
Section: Influence Of Subject and Task Parameters On Effort Perceptionsupporting
confidence: 90%
“…In addition to ensuring comfort, the reliable estimation and reporting of effort perception may be useful in evaluating potential links between physical exposures and risk of musculoskeletal outcomes. Yeung et al (2003) suggested that odds and risk ratios for these outcomes in the shoulder are more closely related to perceived effort than work dissatisfaction, for instance.…”
Section: Introductionmentioning
confidence: 97%
“…This was true for men and women separately and for all subjects as a group [31]. There was, however, a difference between the results for men and women in the correlations of the activity of individual muscles with the Borg score.…”
Section: Correlation Between Normalized Rms and Borg Ratingsmentioning
confidence: 60%
“…The main finding of the above study was that the multiplicative structure of the RNLE is better than an additive model, but the weighting of the RNLE multipliers needs further investigation (Yeung et al, 2006). In another study, a self-reporting worker-based risk assessment was evaluated against the task variables of the RNLE (Yeung, Genaidy, Deddens, & Leung, 2003). Results of that study demonstrated that the subjective self-reporting risk assessment method appeared to be a promising approach (Yeung et al, 2003).…”
Section: Resultsmentioning
confidence: 99%